Tulsa King. Season one [videorecording (DVD)] - Sheridan, Taylor (Tulsa king [DVD videorecording], 2023)
The series follows New York mafia capo Dwight "The General" Manfredi (Academy Award nominee Sylvester Stallone), just after he is released from prison after 25 years and unceremoniously exiled by his boss to set up shop in Tulsa, Oklahoma. Realizing that his mob family may not have his best interests in mind, Dwight slowly builds a "crew" from a group of unlikely characters, to help him establish a new criminal empire in a place that to him might as well be another planet. This Season one release includes all nine episodes with over 90 minutes of bonus content that goes behind the scenes with the cast and crew in six never before seen making of featurettes.